Microwave-induced bismuth(III)-catalyzed synthesis of linear indoloquinolines. Issue 30 (26th July 2017) - Parvatkar, Prakash T.; Parameswaran, P.S.; Bandyopadhyay, Debasish; Mukherjee, Sanghamitra; Banik, Bimal K.
Graphical abstract: Highlights: An efficient microwave-mediated synthesis of indoloquinolines is reported. Reaction uses an environmentally benign bismuth nitrate as a catalyst. Mechanistically, this one-pot transformation is unique. Proposed plausible mechanism for this one-pot transformation. Abstract: Microwave-induced Bi(NO3 )3 -catalyzed one-pot synthesis of a series of linear indoloquinolines is accomplished under mild reaction conditions. While majority of these examples were carried out under solvent-free conditions, in a few cases, minimal quantity of THF is used as solvent. The methodology involves several unique reaction pathways, providing different linear indolo[2, 3- b ]quinolines in good yields from readily available starting materials and using environmentally benign Bi(NO3 )3 ·5H2 O as catalyst.